Global Research Trends on Postpartum Care for Migrant Women: A Comprehensive Bibliometric Analysis (1983-2024) - Uçar, Tuba; Demir Yıldırım, Ayça; Dereli Yılmaz, Sema; Kaya, Güldane Damla; Çakır-Koçak, Yeliz; Koçak, Yeliz Çakır (Springer, 2025)
Postpartum is critical for maternal and newborn health, particularly for immigrant women who may experience unique barriers related to language, cultural differences, and access to healthcare. This study aims to analyse global research trends on postpartum period for immigrant women using bibliometric methods, identify key contributors, and highlight emerging themes and gaps in the literature. A bibliometric analysis was conducted using Web of Science databases. Relevant studies published until December 2024 were retrieved using specific keywords related to postpartum period and immigrant women. The data were analysed using VOS viewer (Visualization of Similarities viewer software) and Bibliometrics for citation analysis, co-authorship networks, and keyword co-occurrence mapping. The number of publications has shown a steady increase since 2008. The most influential journals include BMC Pregnancy and Childbirth and the Journal of Immigrant and Minority Health, with Collins and colleagues in 2011 as the most referenced study. Leading countries in research output are Canada, the United States and the United Kingdom, with strong international collaborations between the University of Toronto, Johns Hopkins University and the University of Oxford. Thematic analysis, based on the co-occurrence of author keywords, revealed five main research clusters: postpartum depression with social support; migration with perinatal care; breastfeeding with cultural adaptation; mental health with inequities in access to care; and maternal well-being with postpartum anxiety. The findings highlight significant advancements in research but also reveal critical gaps in intervention studies and culturally tailored postpartum period models. Future research should prioritise more diverse studies exploring immigrant women's lived experiences and the development of evidence-based, culturally sensitive postpartum period policies.
Keywords: Immigrant women; Postpartum period; Maternal health; Bibliometric analysis; Research trends